![](//s1.studylibfr.com/store/data-gzf/701b9c6101beeeacb876502abe267774/1/001172736.htmlex.zip/bg3.jpg)
ω NE={x∈E, ∀y∈
E, ω(x,y) = 0} {0E}
M ω e
•ω
•M
• ∀f∈E∗,∃!x∈E, ∀y∈E, ω(x,y) = f(y)
(i) ⇔(iii)
ψ:
E→E∗
x7→ E→R
y7→ ω(x,y)
ψR
mker(ψ) = NE
ω⇔NE={0E}
⇔ker(ψ) = {0E}
⇔ψ
⇔ψ
⇔ ∀f∈E∗,∃!x∈E, ∀y∈E, ω(x,y) = f(y)
(i) ⇔(ii)
ω⇔NE={0E}
⇔X∈ Mm,1(R)|∀Y∈ Mm,1(R)nt
XMY = 0
⇔∀X∈ Mm,1(R),∀Y∈ Mm,1(R),t
XMY = 0⇒X= 0
⇔∀X∈(R),t
XM = 0 ⇒X= 0⇔∀X∈ Mm,1(R),t
MX = 0 ⇒W= 0⇔ker(t
M) = {0}
⇔t
M
⇔M
E ω
•ω(x,y)∈E2, ω(x,y) = −ω(y,x)